Cubic Polynomial for the Series of Consecutive Cubes under Alternating Signs - Leomarich Fortugaliza Casinillo; Crisanto L Abas (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2021)
This paper aims to develop an elegant formula for the series of consecutive cubes of natural numbers under alternating signs. In addition, this paper investigates the formula under odd and even number of terms and discuss some important findings.Keywords: Consecutive cubes; alternating signs; odd and even terms.2010 Mathematics Subject Classification: 11B13, 11B50, 97I30AbstrakPaper ini bertujuan membangun formula yang elegan untuk deret berganti tanda bilangan-bilangan kubik berurutan. Paper ini juga menyelidiki formula untuk banyak suku ganjil dan untuk banyak suku genap, dan mendiskusikan beberapa temuan penting.Kata kunci:. Bilangan kubik berurutan, berganti tanda, suku ganjil dan suku genap